If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + -55 = 75 Reorder the terms: -55 + -10x = 75 Solving -55 + -10x = 75 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '55' to each side of the equation. -55 + 55 + -10x = 75 + 55 Combine like terms: -55 + 55 = 0 0 + -10x = 75 + 55 -10x = 75 + 55 Combine like terms: 75 + 55 = 130 -10x = 130 Divide each side by '-10'. x = -13 Simplifying x = -13
| x^2+2x+24=12x | | (5x^2z^5-9z^3)(-8x^6z)=0 | | 2/3y=20 | | 5.6x-5.1=1.06 | | (7y^2-4y+1)(8y^2-6y)= | | [-6]= | | 4/5y+7/y-2 | | 2x-5=-55 | | -9(5)= | | 6X-19=89 | | x/-7=-21 | | -12-(-9)= | | h=-16t^2+117.5t+0 | | x/-7=21 | | 2(5/7)(-3/8) | | 14-6x+10-2x=x-11x | | 4x-2y=z | | -8P+9=25 | | -2x-18+3x=-4 | | x^(1/2)=7 | | 63xpi= | | D/-5-6=20 | | 4x^2-3x=(16x-12)/x | | 3.5/9=x/27 | | 22-5C=-8 | | x+7=7x-41 | | T/3+4=-5 | | 6t-11=3t-2 | | -2a+2+3a=8-29 | | X+(-35)=98 | | 7-6p=10 | | 5-y=25 |